2007
DOI: 10.1017/s1355617707070841
|View full text |Cite
|
Sign up to set email alerts
|

The NIH MRI study of normal brain development: Performance of a population based sample of healthy children aged 6 to 18 years on a neuropsychological battery

Abstract: The National Institutes of Health (NIH) Magnetic Resonance Imaging (MRI) Study of Normal Brain Development is a landmark study in which structural and metabolic brain development and behavior are followed longitudinally from birth to young adulthood in a population-based sample of healthy children. The neuropsychological assessment protocol for children aged 6 to 18 years is described and normative data are presented for participants in that age range (N = 385). For many measures, raw score performance improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
212
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(231 citation statements)
references
References 21 publications
(25 reference statements)
17
212
1
1
Order By: Relevance
“…Finally, Casey et al (2008) reported sex differences in three-dimensional mental rotation among kindergartners. Additionally, Waber, DeMoor, Forbs, Almi, Botteron, and Leonard (2007) reported the first wave of findings from the large National Institutes of Health (NIH) Brain Development Study, in which boys outperformed girls on the Block Design subtest, which requires three-dimensional construction of blocks to match a two-dimensional perspective drawing.…”
Section: Specific Cognitive Tasksmentioning
confidence: 99%
“…Finally, Casey et al (2008) reported sex differences in three-dimensional mental rotation among kindergartners. Additionally, Waber, DeMoor, Forbs, Almi, Botteron, and Leonard (2007) reported the first wave of findings from the large National Institutes of Health (NIH) Brain Development Study, in which boys outperformed girls on the Block Design subtest, which requires three-dimensional construction of blocks to match a two-dimensional perspective drawing.…”
Section: Specific Cognitive Tasksmentioning
confidence: 99%
“…Cognitive development is typically described in terms of improvements in accuracy, capacity, or processing speed and is operationalized as mean level of performance across multiple measurements (e.g., Waber et al, 2007). Less is known about the role of within-person variability in development.…”
Section: Introductionmentioning
confidence: 99%
“…These tests were selected as they reportedly assess a range of neurocognitive skills and have been used previously in studies with adolescence and young adults (Conklin et al, 2007;De Luca et al, 2003;Gould et al, 2012;Harvanko et al, 2012;Khurana et al, 2012;Luciana et al, 2009;Waber et al, 2007). A fixed order of tasks was used to ensure tasks that were likely to be more demanding tasks were not presented consecutively to limit potential fatigue.…”
Section: Neurocognitive Functionmentioning
confidence: 99%